Psychological outcomes of evening and night closed‐loop insulin delivery under free living conditions in people with Type 1 diabetes: a 2‐month randomized crossover trial. Issue 2 (28th October 2016) - Kropff, J.; DeJong, J.; del Favero, S.; Place, J.; Messori, M.; Coestier, B.; Farret, A.; Boscari, F.; Galasso, S.; Avogaro, A.; Bruttomesso, D.; Cobelli, C.; et al.
Abstract: Aim: To assess the impact on fear of hypoglycaemia and treatment satisfaction with an artificial pancreas system used for 2 consecutive months, as well as participant acceptance of the artificial pancreas system. Methods: In a randomized crossover trial patient‐related outcomes associated with an evening‐and‐night artificial pancreas and sensor‐augmented pump therapy were compared. Both intervention periods lasted 8 weeks. The artificial pancreas acceptance questionnaire (range 0–90, higher scores better), Hypoglycaemia Fear Survey II (range 0–72, higher scores worse) and Diabetes Treatment Satisfaction Questionnaire (range 0–36, higher scores better) were completed by 32 participants. Semi‐structured interviews were conducted after study completion in a subset of six participants. Outcomes were compared using a repeated‐measuresanova model or paired t ‐test when appropriate. Results: The total artificial pancreas acceptance questionnaire score at the end of the artificial pancreas period was 69.1 (sd 14.7; 95% CI 63.5, 74.7), indicating a positive attitude towards the artificial pancreas. No significant differences were found among the scores at baseline, end of sensor‐augmented pump therapy period or end of the artificial pancreas period with regard to fear of hypoglycaemia [28.2 (sd 17.5), 23.5 (sd 16.6) and 23.5 (sd 16.7), respectively; P = 0.099] or diabetes treatment satisfaction [29.0 (sd 3.9), 28.2 (sd 5.2) and 28.0 (sd 7.1), respectively; P = 0.43]. Themes frequently mentioned in the interviews were 'positive effects at work', 'improved blood glucose', 'fewer worries about blood glucose', but also 'frequent alarms', 'technological issues' and 'demand for an all‐in‐one device'. Conclusions: The psychological outcomes of artificial pancreas and sensor‐augmented pump therapy were similar. Current artificial pancreas technology is promising but user concerns should be taken into account to ensure utility of these systems. What's new?: To our knowledge this is the first study to examine the treatment satisfaction and acceptance of an artificial pancreas system using validated questionnaires and semi‐structured interviews in a long‐ term, randomized crossover trial in people with Type 1 diabetes. Although participant acceptance of the artificial pancreas was high, no improvement in treatment satisfaction was found compared with sensor‐augmented pump therapy. Participants appear to appreciate the positive effects on glucose regulation but technical errors and reduced usability diminish their appreciation for the system. Our results provide further insight into patient acceptance of current artificial pancreas technology and signifies the need for further development of the technology before commercialization.